Peran Humas PT Kereta Api Indonesia (Persero) di Kota Medan Dalam Meningkatkan Jumlah Penumpang Kereta Api di Era Pandemi - Jumaidi, Jumaidi; Nurhanifah, Nurhanifah; Husna, Ade Humairoh; Rantika, Milla; Hasibuan, Yumna Wiladah; Wafa, Aulia (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study examines the role of humans in increasing KAI Medan passengers. This study uses a qualitative method. The results of this study show that PT KAI through its three strategic steps, namely adaptive, solutive and collaborative, has made a number of adaptations during the pandemic. We should appreciate the conditions that have been implemented, including by supporting PT KAI's condition to boost the performance of freight or passenger transportation. Keywords: Role, Public Relations, Number of Passengers